2017
DOI: 10.1007/978-1-4939-7407-8_15
|View full text |Cite
|
Sign up to set email alerts
|

Anterograde Tract Tracing for Assaying Axonopathy and Transport Deficits in Glaucoma

Abstract: Whether to stage degeneration or investigate early pathology in glaucoma, examination of axonal structure and function is essential. There are a wide variety of methods available to investigators using animal models of glaucoma, with varying utilities depending on the questions asked. Here, we describe the use of anterograde neuronal tract tracing using cholera toxin B (CTB) for the determination of axon transport integrity of the retinofugal projection. This method reveals the structure of the retinal axons a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…In this study, significant reductions in PERG P1 and N2 amplitudes occurred at younger ages in 3xTg mice, and with greater severity than agematched controls. These perturbations in 3xTg mouse RGC function did not likely result from upstream loss of outer retinal cell input to RGCs, as our fERG data confirmed that 3xTg mice exhibited normal photoreceptor responses [105,106]. Additionally, fERG data indicated that both 3xTg and control mice exhibited normal age-related changes in the function of bipolar cells-the interneurons conveying visual signals between photoreceptors and RGCs [114].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In this study, significant reductions in PERG P1 and N2 amplitudes occurred at younger ages in 3xTg mice, and with greater severity than agematched controls. These perturbations in 3xTg mouse RGC function did not likely result from upstream loss of outer retinal cell input to RGCs, as our fERG data confirmed that 3xTg mice exhibited normal photoreceptor responses [105,106]. Additionally, fERG data indicated that both 3xTg and control mice exhibited normal age-related changes in the function of bipolar cells-the interneurons conveying visual signals between photoreceptors and RGCs [114].…”
Section: Discussionsupporting
confidence: 65%
“…SC images were taken with a 5x objective at a resolution of 1.3 m × 1.3 m per pixel. Integrity of axonal transport was determined by percent area fraction coverage of CTB tracer across the rostrocaudal extent of superficial SC and was computed using a custom-built macro [93,106] for NIH Image J [93,106]; this macro is freely available for use via this reference [93]. The integrity of RGC synaptic terminal distribution across the superficial SC was determined by computing percent area fraction of VGlut2 label in the same way [107].…”
Section: Microscopy and Quantification Of Rgc Density And Axonal Tran...mentioning
confidence: 99%
“…We evaluated transport of cholera toxin subunit B (CTB) from the retina to the superior colliculus (SC), the primary central projection for RGCs in rodents, in rats that received vehicle or BIRB 796 as anterograde axonal transport is compromised early in models of glaucoma 4,[41][42][43][44] . We verified RGC uptake and initial transport of fluorescently labeled CTB in RGC axons from naïve, vehicle-saline, vehicle-microbead, BIRB 796-saline and BIRB 796-microbead retinas ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Deficits in anterograde transport to ganglion cell axonal targets in subcortical structures is an early response to elevated IOP in rodent models of glaucoma that precedes frank axon degeneration in the optic nerve; both precede ganglion cell body loss in the retina 2,13,36 . While in rodents the majority (~95%) of ganglion cells axons project contralaterally, ganglion cells in SMs and other primates project ipsilaterally and contralaterally in about equal (50:50) proportion 37 .…”
Section: Resultsmentioning
confidence: 99%